2021
DOI: 10.1017/s1479262121000472
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pathotype-specific resistance to broad bean wilt virus 2 and cucumber mosaic virus in pepper (Capsicum annuum L.)

Abstract: Two aphid-transmitted RNA viruses, broad bean wilt virus 2 (BBWV2) and cucumber mosaic virus (CMV), are the most prevalent viruses in Korean pepper fields and cause chronic damage in pepper production. In this study, we employed a screening system for pathotype-specific resistance of pepper germplasm to BBWV2 and CMV by utilizing infectious cDNA clones of different pathotypes of the viruses (two BBWV2 strains and three CMV strains). We first examined pathogenic characteristics of the BBWV2 and CMV strains in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…However, from a management perspective, the exact source, whether virus or vector, of the disease is likely less important, and the fact that farmers are already knowledgeable about the association of the presence of aphids and then the later appearance of a disease is a critical first step in developing sound management strategies. However, the first step in IPM is the use of host resistant varieties, and although host resistance to the major viral diseases detected in this study has been previously reported (Heo et al 2021;Ruffel et al 2005), resistance to arthropod pests, especially aphids, is rare (Frantz et al 2004). The successful deployment of virus-resistant cultivars as a management strategy in Benin will require that farmers be better educated about viruses.…”
Section: Discussionmentioning
confidence: 67%
“…However, from a management perspective, the exact source, whether virus or vector, of the disease is likely less important, and the fact that farmers are already knowledgeable about the association of the presence of aphids and then the later appearance of a disease is a critical first step in developing sound management strategies. However, the first step in IPM is the use of host resistant varieties, and although host resistance to the major viral diseases detected in this study has been previously reported (Heo et al 2021;Ruffel et al 2005), resistance to arthropod pests, especially aphids, is rare (Frantz et al 2004). The successful deployment of virus-resistant cultivars as a management strategy in Benin will require that farmers be better educated about viruses.…”
Section: Discussionmentioning
confidence: 67%